Doctrine, Adaptation, and the Fidelity Urge - Liam Miller (Religions)
This paper identifies and critiques the way conceptions of fidelity and reproduction shape contemporary approaches to doctrine. As an interdisciplinary work, I draw tools from adaptation studies, queer theory, and theatrical practice. This allows me to demonstrate how, in recent debates over doctrinal expansion or inclusion, both liberal and conservative approaches operate within the logics of the fidelity urge and reproductive futurism. The result of these commitments is an emphasis on handing on the past to the future. The work of Paleo-Orthodox theologian Thomas Oden, and the recent debates over marriage rites in the Uniting Church in Australia serve as illustrations. In suggesting an alternative, I turn again to the theatrical practices of adaptation to resource new conceptions of fidelity (and, in turn, novelty and transgression) that resist a dichotomy between a stable, unified origin and dependent, derivative copies. In their stead, I connect the bisexual epistemology of Marcella Althaus-Reid to the task of doctrine. Such a move brings the present into focus, resisting the allure of reproduction through a doctrinal agenda of confusion, effusiveness, and obscenity. Doctrine, outside of the fidelity urge, is suggested to be an act of non-competitive adaptation, whose horizon is not bound by the past or beholden to the future but is directed to the needs of the present.